Manajemen Produksi Siaran Berita "Seputar Jogja" Pada Televisi Lokal Jogja TV - hidayah, nurul (JURNAL KOMUNITAS, 2024)
The news programs of private television stations in Indonesia are growing rapidly, making private television stations in Indonesia compete for the attention of the public. In the television broadcast media industry, competition is basically competition to win the attention of the audience. By having a diverse audience, Jogja TV makes innovations to meet the needs of its audience. One of them is by presenting a news program such as the Seputar Jogja program. Even though entertainment programs have a higher level of audience, news programs are still very important to fulfill the audience's information needs regarding events occurring in the Yogyakarta area and its surroundings. This research uses a qualitative approach with descriptive study methods to analyze the objects studied. The descriptive method is a method that only describes situations and events. The research results show that the Seputar Jogja news program went through pre-production, production and post-production stages.